Analysis of 'One-Town One-Product' model as a tool for poverty alleviation in Sultan Kudarat, Philippines - Ellson, Adela; Romo, Glory Dee A.; Traje, A.; Sarmiento, J.M.; Jara, F.I.; Ebarle, E.J.; Merced, D.E. (2012)
Poverty has been one of the major considerations in the Philippine government's blueprint for investment. In the annual Investment Priorities Plan (IPP), the government has concentrated on the sectors enumerated in the Medium-Term Philippine Development Plan (MTPDP) 2004-2010. The goal was to lower poverty level through the periodic development plans. This started in the 1987-1992 Development Plan. To address the poverty issue, the plan intended to develop at least two million hectares of agribusiness land within the six-year period to generate two million jobs and to increase availability of food at reasonable prices.
In Mindanao, with the highest number of poor provinces, nine commodities were prioritized for development. Commodity road maps were crafted for theses commodities to facilitate the achievement of the following goals of the Agricultural Fisheries Modernization Act (AFMA): food security, poverty alleviation, social equity, global competitiveness, and resource sustainability. The aim was to create one million jobs in the rural sector. The product-specific program in line with this is the One-Town One-Product (OTOP) which was patterned after the One Product, One Village model in Japan. One of these commodities is oil palm.
This paper highlights palm oil as an example to illustrate the impact of its promotion on poverty level. It concentrates on Sultan Kudarat as one of the provinces in Mindanao which was found to be the eighth poorest province in the country in 2000, rising from the 38th rank in 1997. Palm oil is the commodity considered in Sultan Kudarat's OTOP. The paper generally aims to assess the impact of this product on the intended beneficiaries in terms of poverty level. Secondary data were used for the analyses. These data were sourced from various literature and agencies. Primary data were gathered through interviews with 87 oil palm growers and other key actors in the oil palm industry using semi-structured questionnaires.
The results show that many small-scale farmers benefit from oil palm growing. About 56 percent of the respondents have farm areas of 5 hectares or less. Other related studies, however, suggest that farm experience and farm size are significantly related to monthly income. It is ascertained that there is a need for technical assistance and sourcing of finance in their operations since farming activities are restricted and return on investment is not immediate.
Keywords: Poverty reduction -- Government policy; Poverty -- Sultan Kudarat (Mindanao); Palm oil; Palm oil industry